A woman's work is never done - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Romain Mirindi of Projet Kaliba, BP 136, Cyangugu, Rwanda, reminds us of the heavy burden of the African woman farmer: 'She rises at 5.30 am to prepare perhaps a breakfast that she will eat with her family later in the morning. Then she goes to work...